Exosomal miRNAs as novel avenues for breast cancer treatment - Singh, Tejveer; Kaushik, Mahesh; Mishra, Lokesh Chandra; Behl, Chesta; Singh, Vijay; Tuli, Hardeep Singh (Frontiers in Genetics, 2023)
Breast cancer is the most commonly diagnosed cancer and a leading cause of death in women worldwide. It is a heterogeneous disease as shown by the gene expression profile in breast cancer sample. It begins in milk-producing ducts, with a high degree of diversity between and within tumors as well as among cancer-bearing individuals. The enhanced prevalence of breast cancer is influenced by various hormonal, lifestyle, and environmental factors, and very early onset of the disease correlates strongly with the risk of local and distant recurrence. Many subtypes are difficult to treat with conventional therapeutic modalities and therefore, optimal management and early diagnosis is the first step to minimize the mortality linked with breast cancer. The use of newer methods of nanotechnology extends beyond the concept of synthesizing drug delivery mechanisms into the creation of new therapeutics, such as delivering chemotherapeutics with nanomaterial properties. Exosomes, a class of nanovesicles, are emerging as novel tools for deciphering the patient-specific proteins and biomarkers across different disease models including breast cancer. In this review we address, the role of exosomal miRNA as diagnosis, and treatment for breast cancer therapy.